PELAKSANAAN UPACARA ADAT BIBU BIYAU PADA MASYARAKAT DAYAK HIBUNT DI DESA KELOMPU - NIM. A1012201053, KALISTA APRILIA YOLANDA (Jurnal Fatwa Hukum, 2024)
Abstrac  The marriages of the Dayak Hibunt Community in Kelompu Village, Kembayan District, Sanggau Regency cannot be separated from their relationship with parents, family or relatives, ancestral spirits, or society. Even in the implementation of traditional marriage ceremonies there are still things related to the supernatural, respecting ancestors or forefathers. The implementation of traditional marriage ceremonies which are carried out according to tradition is to maintain and preserve the marriage customs of the Hibunt Dayak Community in Kelompu Village, Kembayan District, Sanggau Regency so that they remain preserved, even though they are experiencing shifts.The problem formulation is "Is the implementation of the "Bibu Biyau" Traditional Ceremony in the Dayak Hibunt Community in Kelompu Village, Kembayan District, Sanggau Regency Still Being Carried Out in Accordance with the Original Provisions". The method used in this research is an empirical writing method with descriptive research characteristics, namely conducting research by describing the situation as it existed when this research was carried out until drawing final conclusions. Data collection tools using interviews and questionnaires with traditional stakeholders and families who use the "Bibu Biyau" custom in Kelompu Village, Kembayan District, Sanggau Regency.The results of the research achieved are that the implementation of the "Bibu Biyau" traditional ceremony in the Dayak Hibunt Community in Kelompu Village, Kembayan District, Sanggau Regency is still being carried out even though it has experienced shifts, such as being carried out for seven days and seven nights, now only two to three hours have been completed, that is the factor that causes it to occur. The shift in the implementation of the "Bibu Biyau" traditional ceremony in the Dayak Hibunt community is economic constraints, difficulty finding a set of tools as a requirement for the "Bibu Biyau" traditional ceremony, that the legal consequences for those who do not carry out the "Bibu Biyau" traditional ceremony are subject to customary sanctions by paying a fine. in the form of taels, and that the legal effort made by traditional functionaries to preserve the culture that has been carried out since the time of their ancestors is to appeal to the community to work together to protect this heritage, especially young people, not to forget traditions even though times have developed like now.Keywords: Hibunt Dayak Tradition, Traditional Ceremony, Marriage.  Abstrak  Perkawinan Masyarakat Dayak Hibunt di Desa Kelompu Kecamatan Kembayan Kabupaten Sanggau tidak terlepas hubungannya   dari   orang tua, keluarga atau sanak saudara, roh leluhur, maupun masyarakat. bahkan didalam pelaksanaan upacara adat perkawinan itu masih terdapat hal-hal yang bersangkutan dengan hal ghaib, menghormati leluhur atau nenek moyang. Pelaksanaan upacara adat perkawinan yang dilaksanakan secara adat adalah untuk menjaga dan melestarikan adat istiadat perkawinan Masyarakat Dayak Hibunt Di Desa Kelompu Kecamatan Kembayan Kabupaten Sanggau agar tetap terpelihara kelestariannya, walau mengalami pergeseran.Adapun rumusan masalahnya "Apakah Pelaksanaan Upacara Adat "Bibu Biyau" Pada Masyarakat Dayak Hibunt Desa Kelompu Kecamatan Kembayan Kabupaten Sanggau Masih Dilaksanakan Sesuai Dengan Ketentuan Aslinya". Metode yang digunakan dalam penelitian ini adalah metode penulisan empiris dengan sifat penelitian deskriptif, yaitu mengadakan sifat penelitian dengan cara menggambarkan keadaan sebagaimana adanya pada saat penelitian ini dilakukan sampai mengambil kesimpulan akhir. Alat pengumpulan data dengan wawancara dan kuesioner kepada pihak Pemangku Adat, dan Keluarga yang Menggunakan Adat "Bibu Biyau" di Desa Kelompu Kecamatan Kembayan Kabupaten Sanggau.Hasil penelitian yang dicapai adalah bahwa pelaksanaan upacara adat "Bibu Biyau" Pada Masyarakat Dayak Hibunt Desa Kelompu Kecamatan Kembayan Kabupaten Sanggau masih tetap dilakukan walaupun mengalami pergeseran seperti dilaksanakan selama tujuh hari tujuh malam sekarang hanya dua hingga tiga jam saja sudah selesai, bahwa faktor penyebab terjadinya pergeseran pelaksanaan upacara adat "Bibu Biyau" pada masyarakat Dayak Hibunt adalah kendala ekonomi, kesulitan mencari seperangkat alat-alat sebagai syarat upacara adat "Bibu Biyau", bahwa akibat hukum bagi yang tidak melaksanakan upacara adat "Bibu Biyau" dikenakan sanksi adat dengan membayar denda berupa tael, dan bahwa upaya hukum yang dilakukan oleh fungsionaris adat dalam melestarikan budaya yang sudah dilakukan sejak zaman nenek moyang adalah dengan menghimbau kepada masyarakat agar sama-sama menjaga warisan tersebut, terutama anak-anak mudanya jangan sampai melupakan tradisi walaupun zaman sudah berkembang seperti sekarang.Kata Kunci : Adat Dayak Hibunt, Upacara Adat, Perkawinan.